THERMODYNAMIC EVALUATION OF A TWO STAGES COMPRESSION REFRIGERATION SYSTEM INTEGRATED TO AN ABSORPTION SYSTEM - Corrêa, G. A.; Souza, J. A.; Prentice-Hernández, C.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2008)
This work is based on the principles of administration, with technical and economic data from a frigorific fishing industry, at analyzing the convenience of integrating to the existing refrigeration system (by vapor compression) a refrigeration system by absorption. By comparing the existing system, and this one integrated with absorption, it was applied a thermodynamic evaluation for a mean frigorific output of 33.43 kW. The profitable result obtained from this evaluation indicated the feasibility of the integrated refrigeration system, with an operation time of up to 25.64 %, less than the existing refrigeration system, enabling a lower amount of time for investment return than five years. In the evaluation, they were compared the energetic model, associating energy and the operation cost. The highest profitability of integrated system shows, for the system applied in the industry, that by applying such system it contributes to lower the operations costs, with further results of increased in the product offer, and competitiveness in marketing frigorific items.